Na⁺ transporter, TaHKT1;5‐D, limits shoot Na⁺ accumulation in bread wheat - Byrt, Caitlin Siobhan; Xu, Bo; Krishnan, Mahima; Lightfoot, Damien James; Athman, Asmini; Jacobs, Andrew Keith; Watson‐Haigh, Nathan S; Plett, Darren; Munns, Rana; Tester, Mark; Gilliham, Matthew (The Plant journal : for cell and molecular biology, 2014)
Bread wheat (Triticum aestivum L.) has a major salt tolerance locus, Kna1, responsible for the maintenance of a high cytosolic K⁺/Na⁺ ratio in the leaves of salt stressed plants. The Kna1 locus encompasses a large DNA fragment, the distal 14% of chromosome 4DL. Limited recombination has been observed at this locus making it difficult to map genetically and identify the causal gene. Here, we decipher the function of TaHKT1;5‐D, a candidate gene underlying the Kna1 locus. Transport studies using the heterologous expression systems Saccharomyces cerevisiae and Xenopus laevis oocytes indicated that TaHKT1;5‐D is a Na⁺‐selective transporter. Transient expression in Arabidopsis thaliana mesophyll protoplasts and in situ polymerase chain reaction indicated that TaHKT1;5‐D is localised on the plasma membrane in the wheat root stele. RNA interference‐induced silencing decreased the expression of TaHKT1;5‐D in transgenic bread wheat lines which led to an increase in the Na⁺ concentration in the leaves. This indicates that TaHKT1;5‐D retrieves Na⁺ from the xylem vessels in the root and has an important role in restricting the transport of Na⁺ from the root to the leaves in bread wheat. Thus, TaHKT1;5‐D confers the essential salinity tolerance mechanism in bread wheat associated with the Kna1 locus via shoot Na⁺ exclusion and is critical in maintaining a high K⁺/Na⁺ ratio in the leaves. These findings show there is potential to increase the salinity tolerance of bread wheat by manipulation of HKT1;5 genes.